A Realidade das Decisões sobre Liberdade de Expressão, Honra e Imagem no STF e no STJ - Hartmann, Ivar (2019)
The problem of foreseeability on what speech is allowed in a specific legal system is directly related to chilling effect. That is, the cost for society of fewer opinion being expressed due to uncertainty on whether the author will later be punished. It is not merely about the role of producing precedent that will make the STF and STJ jurisprudence on the rights to speech, honor and image more predictable, but also that of generating authoritative material which increases the chances that lower courts will adopt workable precedents. The study seeks to answer the question: what are the conditions for quality of the STF and STJ performance in this role? The research problem is subdivided into four parts: i) how often do these courts rule on the matter?; ii) what is the timing of these rulings?; iii) the rulings are produced under conditions that allow judges careful and complete analysis of the facts and legal issues in the case?; iv) are the rulings issues by the STF and STJ as collegiate (full bench or chamber) bodies, according to constitutional requirement? The results indicate that the high courts deal with a workload that renders impossible any chance of analysis of the legal and constitutional law applied to the case under review. The conditions under which the judges work prevent the quality of the rulings. The courts do not decide as collegiate bodies and have instead transformed in a group of individual rulings.